ANALISIS SEMIOTIKA ROLAND BARTHES MENGENAI KETIDAKADILAN GENDER DALAM FILM YUNI - Arneta Huril Hasanah; Oki Achmad Ismail (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this research is to understand the meaning of the forms of gender injustice contained in Yuni's film. The research method used is qualitative research by applying Roland Barthes' semiotic analysis technique, which consists of three levels of meaning, namely denotation, connotation, and myth. In order to achieve the research objectives, the scenes and dialogues that contain gender injustice against women in the film are analyzed and divided into eight units of analysis. The results of the study show that the female characters in Yuni's film experience various forms of gender injustice, including marginalization, subordination, stereotypes, violence, and double burdens. This gender injustice occurs because of the existence of patriarchal ideology adhered to by women leaders and the community in the environment where they live. The strong patriarchal culture causes the powerlessness of female figures who live in rural areas to fight the injustice they experience.